Diversity-oriented synthesis of imidazo[2, 1-a]isoquinolines. Issue 73 (2nd August 2018) - Mai, Shaoyu; Luo, Yixin; Huang, Xianyun; Shu, Zhenghao; Li, Bingnan; Lan, Yu; Song, Qiuling
Abstract : Herein, we report an efficient and practical strategy for the synthesis of five types of imidazo[2, 1- a ]isoquinolines via Cp*Rh III -catalyzed [4+2] annulation of 2-arylimidazoles and α-diazoketoesters, whose structural and substituted diversity at 5- or 6-position can be precisely controlled by the α-diazoketoester coupling partners. Abstract : Herein, we report an efficient and practical strategy for the synthesis of five types of imidazo[2, 1- a ]isoquinolines via Cp*Rh III -catalyzed [4+2] annulation of 2-arylimidazoles and α-diazoketoesters, whose structural and substituted diversity at 5- or 6-position can be precisely controlled by the α-diazoketoester coupling partners. Compared with previous reports, in this study, we merged two attractive C–C cleavage strategies (retro-Claisen and decarboxylation) into the classical C–H functionalization/condensation process by choosing appropriate ester groups (–COOEt, –COO t Bu or –COOiPr) or inexpensive additives (HOAc or KOAc). Moreover, the synthetic efficacies of these methods were demonstrated by the concise synthesis of several bioactive compounds and the late-stage modification of representative drugs.